Evaluation of clinical interventions made by pharmacists, doctors and nurses in a hospital post-discharge telephone service: a retrospective cohort study - Kum Chuan Leong; Darshana Meanger; Philip Wu; Alex Wong; Wee Tjun Tee; Michelle Simango; Bianca Levkovich (International Journal of Clinical Pharmacy, 2026)
Abstract Introduction Clinician-led post-discharge telephone follow-up programs are effective in resolving medication-related problems (MRPs) in older adults. Our hospital offers a post-discharge telephone service, Talk-To-You-Tomorrow (TTYT), to general medicine patients to support medication management following hospital discharge. However, little is known about the the types of interventions used to address MRPs between clinicians within post-discharge telephone services. Aim To compare the types of interventions utalised (pharmacists versus non-pharmacist clinicians) in addressing MRPs for general medicine patients identified through a post-discharge telephone follow-up (TFU) service. Method A retrospective cohort study investigated interventions provided to general medicine patients between June 2022 to May 2023 who underwent TTYT in a large metropolitan health service. Contemporaneous records were used to identify patients with MRPs and there corresponding interventions. MRPs were categorised using the Drug Evaluation Tools (NESA: necessity, effectiveness, safety and adherence). Interventions were classified using The Swiss Society of Public Health Administration and Hospital Pharmacists tools (patient-level, prescriber-level, drug-level and other interventions). Primary outcome was the difference in interventions (pharmacists versus non-pharmacist clinicians). Secondary outcome was the types of MRPs identified by different clinicians. Outcomes were evaluated using the Pearson’s χ 2 test. Odds of MRP identification by clinician group were estimated with an adjusted odds ratio (OR) and 95% confidence interval (CI). Results From 3,815 TTYT consultation records, 526 patients had MRPs. All MRPs had at least one intervention (227 pharmacist's and 299 non-pharmacist clinicians'). Pharmacists liaised with other clinicians the most (7.9% (18/227) vs 4.7% (14/299)) versus non-pharmacist clinicians who utilised more drug-level interventions (18% (53/299) vs 13.2% (30/227)). There were no statistically significant differences in the intervention types across pharmacists versus non-pharmacists (X 2 (3, N = 526) = 4.271, p = 0.234) and MRP types identified by different clinicians (X 2 (6, N = 526) = 11.777, p = 0.067). The odds of a pharmacist identifying an MRP was 2.27 times greater than non-pharmacists (p < 0.001, CI: 1.82–2.82). Conclusion Clinicians mostly provided patient-level interventions however, no difference in the types of MRP’s identified in a post-discharge TTYT consult between various clinicians. Importantly, pharmacists were more likely identifying a MRP than other clinicians, which highlights the beneficial role of a pharmacist in medication management and their impact on medication safety.